Challenges for a complex comparative analysis: problematizing educational data in the context of the Covid pandemic 19 in Campinas (SP) - Brazil - Juliano Pereira de Mello; Artur Renda Vitorino (Pontificia Universidad Católica del Perú, 2021)
This work aims to problematize the impacts of Pandemic Covid 19 in the elementary school of the Municipal Education Network of Campinas (RMEC) considering a brief comparative analysis between two municipal schools regarding the performance or not of non-classroom activities offered by them, in the light of the educational legislation in force and, mainly, from the discussion proposed in a comparative education with a complex and systemic approach, from the pedagogical and political clashes for the democratization of teaching, from the use of data in a contextualized way and not only as carriers of a neutral and unquestionable rationality and the elements of an aesthetic mode of existence present in the documents and actions implemented in the context of the closure of schools due to the Covid Pandemia 19.